The Effect of Bajakah Wood Extract on Collagenase Activity of Glycated Proteins in Rats and its Review from an Islamic Perspective - Ainuzzahra; Harliansyah; Nenden Lilis Setiasih; Luh Ade Lela Arika; Puput Putuh Anisa (Green Publisher Indonesia, 2026)
Skin aging is a biological process that is influenced by oxidative stress and the accumulation of advanced glycation end products (AGEs) that can increase the activity of the collagenase enzyme so that it causes collagen degradation. Red logan wood (Spatholobus littoralis Hassk.) is known to have antioxidant content that has the potential to inhibit this process. This study aimed to determine the effect of administration of ethanol extract of red logs on collagenase activity in male white rats of the Sprague-Dawley strain induced by D-galactose. This study is a laboratory experimental research with a post-test only control group design. A total of 36 rats were divided into six groups, namely the blank group, negative control, positive control, and three treatment groups given red bajakah wood ethanol extract with doses of 25 mg/kgBB, 50 mg/kgBB, and 100 mg/kgBB. Induction of aging was carried out using D-galactose, then serum collagenase activity was measured using the ELISA method. Data were analyzed using a one-way ANOVA test followed by an LSD test with a significance level of p < 0.05. The results showed that the administration of ethanol extract of red logs was able to significantly reduce collagenase activity compared to the negative control group (p < 0.05). Doses of 100 mg/kgBB showed the greatest decreasing effect and were close to positive control groups. This suggests that red logwood extract has the potential to be a natural anti-aging agent through a mechanism of inhibition of collagen activity.